2017
DOI: 10.1017/s0022215117002031
|View full text |Cite
|
Sign up to set email alerts
|

Initial assessment in the management of adult epistaxis: systematic review

Abstract: Sustained ambulatory hypertension, anticoagulant therapy and posterior bleeding may be associated with recurrent epistaxis, and should be recorded. Oral ice pack use may decrease severity and can be considered as first aid. Coagulation studies are appropriate for patients with a history of anticoagulant use or bleeding diatheses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 24 publications
0
42
0
Order By: Relevance
“…(8) The clinician should treat patients with an identified site of bleeding with an appropriate intervention, which may include 1 or more of the following: topical vasoconstrictors, nasal cautery, and moisturizing or lubricating agents. (9) When nasal cautery is chosen for treatment, the clinician should anesthetize the bleeding site and restrict application of cautery only to the active or suspected site(s) of bleeding. (10) The clinician should evaluate, or refer to a clinician who can evaluate, candidacy for surgical arterial ligation or endovascular embolization for patients with persistent or recurrent bleeding not controlled by packing or nasal cauterization.…”
mentioning
confidence: 99%
“…(8) The clinician should treat patients with an identified site of bleeding with an appropriate intervention, which may include 1 or more of the following: topical vasoconstrictors, nasal cautery, and moisturizing or lubricating agents. (9) When nasal cautery is chosen for treatment, the clinician should anesthetize the bleeding site and restrict application of cautery only to the active or suspected site(s) of bleeding. (10) The clinician should evaluate, or refer to a clinician who can evaluate, candidacy for surgical arterial ligation or endovascular embolization for patients with persistent or recurrent bleeding not controlled by packing or nasal cauterization.…”
mentioning
confidence: 99%
“…107 One randomized controlled trial of cautery for nosebleed showed bipolar cautery to be less painful with faster healing than monopolar cautery. 9 Cautery may be performed with topical administration of chemically active agents, such as silver nitrate (25%-75%), chromic acid, or trichloroacetic acid, or through the application of heat or electrical energy, typically electrocautery or ''hot wire'' thermal cautery. Sites for application of cautery can range from the small anterior septal vessels in Kiesselbach's plexus to named larger arteries, such as the sphenopalatine artery and its branches located posterior in the nose.…”
Section: Supporting Textmentioning
confidence: 99%
“…(8) The clinician should treat patients with an identified site of bleeding with an appropriate intervention, which may include one or more of the following: topical vasoconstrictors, nasal cautery, and moisturizing or lubricating agents. (9) When nasal cautery is chosen for treatment, the clinician should anesthetize the bleeding site and restrict application of cautery only to the active or suspected site(s) of bleeding. (10) The clinician should evaluate, or refer to a clinician who can evaluate, candidacy for surgical arterial ligation or endovascular embolization for patients with persistent or recurrent bleeding not controlled by packing or nasal cauterization.…”
mentioning
confidence: 99%
“…A strong case for the risk stratification of patients at the time of admission for epistaxis seems appropriate. 3 When one considers these results, and the national study by the Integrate network on epistaxis and mortality, 4 which looked at a 30-day outcome in mortality, the underlying factors were not dissimilar. The Integrate paper reported a mortality rate of 3.4 per cent.…”
mentioning
confidence: 99%